Dexamethasone 0.7 mg implants in the management of pseudophakic cystoid macular edema - Garcia,José Maurício Botto de Barros (2016)
ABSTRACT Pseudophakic cystoid macular edema (PCME) is a common complication following cataract surgery. Although majority of patients with PCME remain asymptomatic, it remains an important cause of vision loss after cataract surgery. The pathogenesis of PCME remains unclear, but most authors agree that inflammation plays a major role in its development. There is no standard algorithm for treatment procedures for PCME. A biodegradable 0.7 mg dexamethasone intravitreal implant can be used to deliver medication into the posterior segment of eyes. This drug acts on all inflammatory mediators and has been approved for the treatment of macular abnormalities secondary to retinal vein occlusion and for non-infectious posterior uveitis. In this case series, we report six patients who presented with PCME and were treated with a 0.7 mg dexamethasone intravitreal implant. Favorable anatomical outcomes were demonstrated by spectral domain-optical coherence tomography images.